2-(2-Fluoro-[1,1′-biphenyl]-4-yl)-N-(4-methyl-2-oxo-2H-chromen-7-yl)propanamide - Stanimir Manolov; Iliyan Ivanov; Dimitar Bojilov; Paraskev Nedialkov (Molbank, 2023)
Herein, we report the synthesis of 2-(2-fluoro-[1,1′-biphenyl]-4-yl)-N-(4-methyl-2-oxo-2H-chromen-7-yl)propanamide in the reaction between 7-amino-4-methyl-2H-chromen-2-one and (±)-flurbiprofen. The newly-obtained bio-functional hybrid compound was fully characterized via 1H, 13C NMR, UV, and mass spectral data.